PERAN MASYARAKAT DALAM MELAKSANAKAN PROGRAM PAMSIMAS DI DESA BANJARSARI KECAMATAN GAJAH KABUPATEN DEMAK - Nofiandi, Hardiles; Taufik, Achmad; Widayati, Wiwik (Journal of Politic and Government Studies, 2014)
ABSTRACTWater as a fundamental requirement for life, should be met in terms ofquantity, quality, affordable, and continuous. But there are still many Indonesianpeople who do not get adequate water, especially low-income people in rural areasand suburbs. Pamsimas is one of the government's flagship program in theprovision of clean water and sanitation to rural and suburban communitiesthrough community-based approaches. This research uses descriptive qualitativemethod of data collection through interview techniques, with purposive samplingmethod of selecting informants.Research results in the participation rate Pamsimas (Water Supply andSanitation Community-Based) in the village of DemakBanjarsari includes 3components. First, program planning; second, the implementation of the program;Third, after the implementation of the program. The three components areinterrelated with one another that can not be separated in order to achieveoutcomes on the role of community in implementing BanjarsariPamsimas in thevillage. Approach or policy to encourage society in the implementation ofPamsimas (Water Supply and Community-Based Sanitasi) has strategies andprinciples consist of: community empowerment and local institutionaldevelopment; improvement of health and hygiene behaviors and sanitationservices; drinking water supply and public sanitation, grants local socio-economicdevelopment; and support the implementation and project management. Theapproach taken is based on: a community-based, participatory, responsive,masyarajat access for all, gender equality, pro poor, sustainability, transparencyand accountability, value-based.Recommendations, the study is expected to maintain and developprograms Pamismas in the village because it is very beneficial to the localcommunity. In addition it is expected that the successful implementation of theprogram in the village BanjarsariPamsimas this can be a reference for beneficiaryvillages Pamsimas other programs.Keywords: Pamsimas, Community Empowerment, Banjarsari Village,District Gajah, Demak